The Effect of Liquidity, Working Capital and Operational Costs on Profitability of Trading Companies Registered in Indonesia Stock Exchange 2013-2015 - Thomas Firdaus Hutahaean (Journal of Research in Business, Economics, and Education, 2020)
This study aims to examine and analyze the effect of liquidity, working capital and operational cost on profitability of trading companies listed on the Indonesia Stock Exchange in 2013-2015 period. The study used a quantitative approach, this type of research is quantitative descriptive by causal relationship. The populations of this study are all registered trading companies in Indonesia Stock Exchange consisting of 55 companies. Samples were drawn by 29 companies, by purposive sampling technique. The analytical method used in this research is multiple linear regression and classic assumption test to get a good regression model. The results of this study indicate that simultaneously liquidity, working capital and operating costs have a significant effect on profitability in trading companies listed on the Indonesia Stock Exchange in 2013-2015 period. Partially, liquidity and working capital have a positive and significant effect on profitability in trading companies listed on the Indonesia Stock Exchange in 2013-2015 period, while operating cost does not  have any effect on profitability. The conclusion of this research states that increase in liquidity and working capital will lead to an increase in profitability. The results obtained from the coefficient of determination of R2 value is 0.330, meaning that profitability variable variation can be explained by variations of variable of liquidity, working capital and operating expenses reaching up to 33% while the rest of 67% is explained by other independent variables.